PROTECTION OF LINEAGE (HIFZ AL-NASL) IN DETERMINING THE LEGAL PARENTAGE OF CHILDREN BORN OUT OF WEDLOCK: A NORMATIVE ANALYSIS AND JUDICIAL PRACTICE OF THE PRINGSEWU RELIGIOUS COURT - Muhammad Aqwam Thariq; Moh. Muhibbin; Nofi Sri Utami (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Focused on the Islamic principle of hifz al-nasl, this study has a dual aim: first, to analyze the framework for establishing the legal parentage of children born out of wedlock, and second, to scrutinize related judicial practices at the Pringsewu Religious Court. The research applies a normative juridical method, utilizing statutory, conceptual, and case study approaches to examine laws, the Compilation of Islamic Law, and court decisions. Analysis is conducted through grammatical and systematic interpretation. According to the study, judicial practice at the Pringsewu Religious Court involves two distinct methods for establishing parental lineage. The first, a normative-preventive method, ties the child's legal status directly to the lawful nature of the parents' marriage, effectively preventing children born from invalid unions from being recognized as legitimate. In contrast, the normative–progressive approach grants legal protection by affirming the child’s biological parentage, ensuring legal certainty, identity, and safeguarding the child’s rights. This practice is concretely reflected in Case Number 57/Pdt.P/2024/PA.Prw and Case Number 28/Pdt.P/2025/PA.Prw, and demonstrates the court's effort to balance the enforcement of Islamic family law norms with child protection in accordance with the principles of maqasid shariah, specifically ḥifẓ al-nasl.